PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI JC VEGETARIAN & COFFEE MEDAN - Melissa; Weny, Weny (Universitas HKBP Nommensen, 2025)
This research aims to determine the effect of product quality and service quality on purchasing decisions at JC Vegetarian & Coffee, Medan. The research employs a quantitative associative approach to measure the relationship between product quality, service quality, and purchasing decisions. A sample of 75 respondents was selected using incidental sampling. The normality test shows a value of 0.200, which is greater than the significance level of 0.05, indicating that the data are normally distributed. The coefficient of determination test reveals that product quality and service quality influence purchasing decisions by 51.265%. Based on the results of the multiple linear regression analysis, the regression equation obtained is Y = 18.488 + 0.218X1 + 0.415X2, meaning that for each unit increase in product quality, purchasing decisions increase by 0.218 times, and for each unit increase in service quality, purchasing decisions increase by 0.415 times. The F-test result shows a significance value of 0.000, which is smaller than 0.05, indicating that product quality and service quality simultaneously affect purchasing decision.